2014
DOI: 10.1016/j.cmet.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of the DLK1-MEG3 MicroRNA Cluster in Human Type 2 Diabetic Islets

Abstract: SUMMARY Type 2 diabetes mellitus (T2DM) is a complex disease characterized by the inability of the insulin-producing β-cells in the endocrine pancreas to overcome insulin resistance in peripheral tissues. To determine if microRNAs are involved in the pathogenesis of human T2DM, we sequenced the small RNAs of human islets from diabetic and non-diabetic organ donors. We identified a cluster of miRNAs in an imprinted locus on human chromosome 14q32 that is highly and specifically expressed in human β-cells and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
298
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(320 citation statements)
references
References 51 publications
17
298
2
3
Order By: Relevance
“…Conversely, several microRNA changes revealed by the screening of human islets were not previously highlighted by the systematic analysis of islets isolated from animal models of diabetes. Indeed, the islets of type 2 diabetic donors were found to express higher levels of miR-187, miR-187*, miR-224 and miR-589 and decreased levels of miR-7, miR-369, miR-487a, miR-655 and miR-656 (see Table 3) [13]. Similar changes in the expression of miR-187 and miR-7a were confirmed by independent research groups [25,34].…”
Section: Can Findings Obtained From Animal Models Of Diabetes Be Extrsupporting
confidence: 65%
See 2 more Smart Citations
“…Conversely, several microRNA changes revealed by the screening of human islets were not previously highlighted by the systematic analysis of islets isolated from animal models of diabetes. Indeed, the islets of type 2 diabetic donors were found to express higher levels of miR-187, miR-187*, miR-224 and miR-589 and decreased levels of miR-7, miR-369, miR-487a, miR-655 and miR-656 (see Table 3) [13]. Similar changes in the expression of miR-187 and miR-7a were confirmed by independent research groups [25,34].…”
Section: Can Findings Obtained From Animal Models Of Diabetes Be Extrsupporting
confidence: 65%
“…One such example is the decrease in islet miR-184 expression observed in several independent animal studies [20,21,29,30]. Although changes in the level of this particular non-coding RNA were not detected on global profiling of a small number of human samples [13,34], they were readily confirmed by a study that focused specifically on miR-184 in which a large number of islet preparations were compared [20].…”
Section: Can Findings Obtained From Animal Models Of Diabetes Be Extrmentioning
confidence: 55%
See 1 more Smart Citation
“…While these protocols are currently dependent upon large quantities of source tissue material in cell culture, this limitation excludes the possibility of studying human islets however the development of the stem cell differentiation protocols may make the CLIP protocol viable for human β-cells in the near future. A recent study profiling miRNAs after the immunoprecipitation of Ago proteins revealed stark differences in the small RNA profile suggesting biochemical approaches to profile miRNAs in FACS-sorted human β-cells may provide insight into distinct populations of miRNAs which interact with specific RNA binding proteins [4] [23]. To date, numerous studies have established specific miRNA:target gene interactions implicating the entire range of β-cell physiology and it appears likely that eventually every functional category (i.e.…”
Section: Identification Of Microrna Targets In the β-Cellmentioning
confidence: 99%
“…The imprinted DLK1-MEG3 gene region is associated with type 2 diabetes (T2DM). Using HITS-CLIP, Vasumathi et al [82] identified disease-relevant targets of miRNAs in the DLK1-MEG3 gene region, implying their roles in T2DM.…”
Section: Decoding Mirna-target Interactionsmentioning
confidence: 99%